2018
DOI: 10.1007/s10633-018-9652-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of varying skin surface electrode position on electroretinogram responses recorded using a handheld stimulating and recording system

Abstract: PurposeA handheld device (the RETeval system, LKC Technologies) aims to increase the ease of electroretinogram (ERG) recording by using specially designed skin electrodes, rather than corneal electrodes. We explored effects of electrode position on response parameters recorded using this device.MethodsHealthy adult twins were recruited from the TwinsUK cohort and underwent recording of light-adapted flicker ERGs (corresponding to international standard stimuli). In Group 1, skin electrodes were placed in a “co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“… 55 It is difficult to compare directly the ERG parameters in different animals under ISCEV standard methods, because there are lots of other factors affecting ffERG, such as eyebyall sizes (size of retinal area), orbital rim thickness, location of electrodes, electodes materials, general anesthesia, and so on. 56 , 57 The implicit time of the a-wave (16.12 ms) and b-wave (41.06 ms) in scotopic 3.0 ERG (rod-cone response) in our study were similar to those reported by Bouskila et al in the rod-cone response of green monkeys (14.8 ms and 36.7 ms, respectively). 58 Furthermore, our ERG results (aged 14 months and weighed 30 kg) were comparable to those of other pig studies and valuable with a relatively larger number of subjects.…”
Section: Discussionsupporting
confidence: 90%
“… 55 It is difficult to compare directly the ERG parameters in different animals under ISCEV standard methods, because there are lots of other factors affecting ffERG, such as eyebyall sizes (size of retinal area), orbital rim thickness, location of electrodes, electodes materials, general anesthesia, and so on. 56 , 57 The implicit time of the a-wave (16.12 ms) and b-wave (41.06 ms) in scotopic 3.0 ERG (rod-cone response) in our study were similar to those reported by Bouskila et al in the rod-cone response of green monkeys (14.8 ms and 36.7 ms, respectively). 58 Furthermore, our ERG results (aged 14 months and weighed 30 kg) were comparable to those of other pig studies and valuable with a relatively larger number of subjects.…”
Section: Discussionsupporting
confidence: 90%
“… 15 18 , 27 The assessment of visual function used in the current study required < 5 min of testing per patient and does not require pupil dilation, 31 dark adaption, or eye-contacting electrodes. 32 The hand-held RET eval device is a turnkey system that can be administered by a technician or medical assistant with minimal training requirements. Addition of measurement of retinal function should enhance the predictive value of AI algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…Photographic images of each eye allowed post-analysis of electrode placement and fixation using a calibrated graticule. Electrode position can affect the amplitude of the ERG signal [65] and eyes for which the electrode position was > 4 mm were excluded. All images were inspected, and the position of the electrode measured with a weighting of 2 mm below the eye set at 0 in the statistical model.…”
Section: Electroretinography (Erg)mentioning
confidence: 99%